Young children's meaning making about the causes of illness within the family context. (January 2013) - McIntosh, Caroline; Stephens, Christine; Lyons, Antonia
In this article we highlight the ways in which young children draw on their family contexts in their meaning making about the causes of illness. Studies of young children's understanding of illness causality have largely focused on the nature of children's knowledge rather than the ways in which children acquire their knowledge. Seeking to advance a socio-constructivist understanding of young children's conceptualization of illness causality, we interviewed five four-year-old children and their family members. Analysis of participants' narrative accounts suggests that young children's illness causality constructions are significantly influenced by the particular illness experiences, illness prevention messages and behavioural rules within families. By identifying and acknowledging young children's meaning making within the socio-cultural context of the family, health practitioners may be better placed to develop effective health education programmes and provide enhanced psychosocial support for young children and their families.